BUSINESS ADMINISTRATION STUDENTS’ NEEDS IN LEARNING ENGLISH - Risnawati - (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2010)
The study aims to identify students’ needs in learning English. Through questionnaires, the students’ needs could be elicited from 192 students, 37 graduate employees, 19 major subject teachers, and five English teachers of Business Administration (BA) department of Politeknik Negeri Sriwijaya. The questionnaire data were analyzed using means, percentages, t-test, and ANOVA and triangulated with the interview results. Four main conclusions can be drawn. First, ESP materials for academic and professional purposes are demanded in English courses because the BA students use four English skills concurrently with English courses for personal and academic purposes and subsequently for future job purposes. Second, the teaching of general English is still needed because the students lack mastery of language aspects (grammar, pronunciation, and vocabulary, particularly technical words) and of reception and production strategies. Third, language skills and knowledge of language aspects and of reception and production strategies can be developed through the integration of a variety of in- and out-of-classroom activities. Fourth, the teaching of four language skills needs to be integrated in each semester; however, the teaching of general English, reading, and listening should be focused in lower semesters, whereas ESP, speaking, and writing should be emphasized in higher semesters.